Musical Citizens: String Teachers' Perceptions of Citizenship Education in the Private Studio - Harrison, Joan (Université d'Ottawa / University of Ottawa, 2013)
This quantitative study explores string teachers’ perceptions of citizenship education and its use in the private lesson. Guided by Westheimer and Kahne’s (2004) model of citizenship education the study sought to identify (a) how private string teachers perceive citizenship education, and (b) the factors that influence these perceptions. Four hundred and fifteen (415) members of the American String Teachers Association (ASTA) participated in this study by completing an on-line survey that contained both closed and open-ended questions. The resulting data was coded and organized according to the survey questions and the conceptual framework. Research findings revealed that, although teachers did not explicitly consider citizenship education a part of their lessons, their intentions and their report on pedagogical practices could be described as citizenship education when viewed through the conceptual framework used in the study. Indeed, nearly all of the participant responses revealed intentions to include attributes of what Westheimer and Kahne refer to as the Personally Responsible Citizen in their music lessons with students. Educating for traits of other types of citizenship was also reported. Factors deemed influential in string teachers’ perceptions of citizenship education included the following: If the teachers had earned certification in Suzuki pedagogy; the number of years of teaching experience; if teachers self-identified as primarily educators, performers, or both; the age of the students who are taught. Additionally, the study addresses teachers’ statements about the use of competitions, dialogue in lessons, and general attitudes about the appropriateness of citizenship education in several different learning environments. The study findings add to a small but growing body of research that furthers understandings of the links between citizenship education and music education. In addition, the findings contribute to our understanding of the complexity of the relationship between private teachers and their students.
Keywords: benefits of music lessons; citizenship education; private music lessons; music education; democratic citizenship; studio instruction; string pedagogy; Suzuki music